PENGARUH ORIENTASI PELANGGAN DAN ORIENTASI PESAING TERHADAP INOVASI PASAR DAN PERTUMBUHAN PENJUALAN PERUSAHAAN MAKANAN DI SURABAYA - Wahyudiono Wahyudiono (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2010)
The aim of the study is to examine the effect of market orientation and competitor orientation to market innovation and sales growth, and the effect of market innovation to the sales growth of food Companies in Surabaya. The population of the study is all big food companies, which are operated until the end of 2008, and located in Surabaya Industrial Estate Rungkut (SIER). This research employs complete enumeration since the number of population is relatively small (23 food companies), whereas the analysis tool is path analysis. The test results indicate that: market orientation has direct, positive and significant effect to market innovation of food companies. Competitor orientation has direct, positive and significant effect to market innovation of food companies. Customer orientation has direct, positive and significant effect to the sales growh of food companies. Competitor orientation has direct, positive and significant effect to sales growh of food companies. The market innovation has direct, positive and significant effect sales grown of food companies. Another important finding shows that market innovation is able to mediate customer orientation and market orientation with growth sales of companies. It means that the presence of market innovation is required to strengthen the effect of customer orientation and competitor orientation to sales growth of companies.